Student's guide for final year project thesis : BSc, MSc, MA, and MBA - Safieddine, Fadi ([United States] : [publisher not identified], 2021)
A final year project represents a demonstration of a student$1 (Bs ability to integrate the knowledge they acquired from more than one course and subject, to produce a final work that shows your readiness to graduate. In many cases, the students are also required to demonstrate the ability to learn new skills on their own. However, the write-up of the final year project has to follow clear academic guidelines that also show: integrity, creativity, organisation, and research skills.s
Section 1. Project structure. -- Section 2. Project Front Page -- Section 3. Abstract -- Section 4. List of Content -- Section 5. List of Figures and Tables -- Section 6. Acknowledgement -- Section 7. Definition of Terms -- Section 8. Chapter One :Introduction -- Section 9. Chapter Two: Literature Review -- Section 10. Chapter Three: Case Study -- Section 11. Chapter Four: Methodology! -- Section 12. Chapter Five: Implementation! -- Section 13. Chapter Six: Evaluation -- Section 14. Chapter Seven: Conclusion -- Section 15. Bibliography -- Section 16. Appendix -- References.
Includes bibliographical references.
Keywords: REPORT WRITING